The politics of technology in higher learning : the role of information technology in the transformation of higher education in South Africa - Rodenacker, Franz (Department of Political Studies, 2024)
The objective of this research is to investigate the effects of the increasing use of IT for learning in HE generally, and with respect to the aims for the transformation of HE in South Africa specifically. This informs the formulation of principles for a socially-compatible implementation and use of IT in HE in SA. The central question guiding this research is what are likely effects of the increasing use of IT in HE, and how they relate to the aims for HE as set out by South African policy makers. This objective is achieved through a review of the theoretical work pertaining to the relationship between technology and society; an examination of the arguments for IT brought forward by proponents; a thorough examination and critique of IT by use of writings of substantivist, educationalists and educational technology experts; and by an examination of the aims for HE as formulated by South African policy makers, the reasons for the use of IT in South Africa and a comparison of these factors with social realities. The social realities of interest are the poor preparation of some South Africans for HE and the inequitable access structures to IT and telecommunications in particular. The research argument is that the reasons for the use of IT in HE are significant indicators for potential effects of IT on HE. The motivations for the use of IT are closely related to the financial pressures that the expansion of HE exerts on the government and institutions for higher learning alike. IT is seen as the means of easing these financial pressures by increasing the economic efficiency and effectiveness of HE. This thesis argues that HE-institutions may thus place greater emphasis on their economic efficiency and financial effectiveness, and suggests that this may be to the detriment of objectives that are not directly economically significant. The integration of IT into South African HE-institutions thus has the potential to have significant adverse effects on some of the aims and goals of transformation of HE in SA. This thesis is based on a thorough examination of the literature on IT in its application for learning in HE, supported by an in-depth interview and frequent participation in electronic discussion forums. Data collection involved library searches, e-mail links, an interview and Internet searches.